DETERMINANT FACTORS OF THE MENSTRUAL CYCLE IN GRADUATE NURSING STUDENTS - Sokhifah; Tin Utami; Arlyana Hikmanti (SABDA EDU PRESS (SEP), 2024)
According to WHO, more than 75% of women experience menstrual disorders and on average occur at the age of 17-29 years. One of the factors that influence the occurrence of irregular menstrual cycles is poor sleep quality. This study aims to determine the relationship between sleep quality and menstrual cycle in undergraduate nursing students at Harapan Bangsa University. This type of research is an analytic survey with a cross sectional design. The population in this study were 316 undergraduate nursing students and a sample of 174 students with Proportional random sampling method. Instruments used Pittsburgh Sleep Quality Index (PSQI) and menstrual cycle questionnaire. Data analysis used bivariate analysis for frequency distribution and univariate data analysis with chi square to determine the relationship. The results of this study obtained the frequency distribution of sleep quality obtained the highest results (79.3%) in the bad category and the menstrual cycle obtained results (67.8%) in the normal menstrual cycle category, with a p value = 0.151 (p> 0.05). The conclusion is that there is no significant relationship between sleep quality and menstrual cycle in Nursing Study Program Undergraduate Students at Harapan Bangsa University